Inisiatif Perempuan Membentuk Environmental Culture sebagai Upaya Mengatasi Perubahan Iklim - Ikhaputri Widiantini; Abby Gina Boang Manalu (Jurnal Perempuan, 2022)
This research discusses the efforts of women in the community as a form of environmental culture in responding to the climate change crisis. The arrogance issue of patriarchal reason has distorted human ability to recognize the main problem of environmental damage. Humans are trapped in the illusion of the domination of reason which seeks to control nature as non-humans. As a result of this arrogance of reason, culture is formed hierarchically dominating nature (non-humans). We offer a change in cultural perspective through the environmental culture raised by Val Plumwood. This culture with an ecological and caring perspective is a form of the feminist ecological thought movement. We use the method of analyzing feminist issues through feminist knowledge standpoints that interact with ecological research methods. We collect data through various media with a focus on telling the experiences of women in dealing with environmental problems. Our analysis comes to the conclusion that concrete initiatives and actions are needed that involve all ecological elements as a form of solidarity. In this way, we no longer glorify humans as the rulers of reason, but rather create critical and creative communities in realizing an environmental culture.